Dexamethasone-(C21-phosphoramide)-[anti-EGFR]: molecular design, synthetic organic chemistry reactions, and antineoplastic cytotoxic potency against pulmonary adenocarcinoma (A549) - Coyne CP; Narayanan L (Dove Medical Press, 2016)
Cody P Coyne,1 Lakshmi Narayanan2 1Department of Basic Sciences, 2Department of Clinical Sciences, College of Veterinary Medicine, Mississippi State University, Starkville, MS, USA Purpose: Corticosteroids are effective in the management of a variety of disease states, such as several forms of neoplasia (leukemia and lymphoma), autoimmune conditions, and severe inflammatory responses. Molecular strategies that selectively “target” delivery of corticosteroids minimize or prevents large amounts of the pharmaceutical moiety from passively diffusing into normal healthy cell populations residing within tissues and organ systems. Materials and methods: The covalent immunopharmaceutical, dexamethasone-(C21-phosphoramide)-[anti-EGFR] was synthesized by reacting dexamethasone-21-monophosphate with a carbodiimide reagent to form a dexamethasone phosphate carbodiimide ester that was subsequently reacted with imidazole to create an amine-reactive dexamethasone-(C21-phosphorylimidazolide) intermediate. Monoclonal anti-EGFR immunoglobulin was combined with the amine-reactive dexamethasone-(C21-phosphorylimidazolide) intermediate, resulting in the synthesis of the covalent immunopharmaceutical, dexamethasone-(C21-phosphoramide)-[anti-EGFR]. Following spectrophotometric analysis and validation of retained epidermal growth factor receptor type 1 (EGFR)-binding avidity by cell-ELISA, the selective anti-neoplasic cytotoxic potency of dexamethasone-(C21-phosphoramide)-[anti-EGFR] was established by MTT-based vitality stain methodology using adherent monolayer populations of human pulmonary adenocarcinoma (A549) known to overexpress the tropic membrane receptors EGFR and insulin-like growth factor receptor type 1. Results: The dexamethasone:IgG molar-incorporation-index for dexamethasone-(C21-phosphoramide)-[anti-EGFR] was 6.95:1 following exhaustive serial microfiltration. Cytotoxicity analysis: covalent bonding of dexamethasone to monoclonal anti-EGFR immunoglobulin did not significantly modify the ex vivo antineoplastic cytotoxicity of dexamethasone against pulmonary adenocarcinoma at and between the standardized dexamethasone equivalent concentrations of 10-9 M and 10-5 M. Rapid increases in antineoplastic cytotoxicity were observed at and between the dexamethasone equivalent concentrations of 10-9 M and 10-7 M where cancer cell death increased from 7.7% to a maximum of 64.9% (92.3%–35.1% residual survival), respectively, which closely paralleled values for “free” noncovalently bound dexamethasone. Discussion: Organic chemistry reaction regimens were optimized to develop a multiphase synthesis regimen for dexamethasone-(C21-phosphoramide)-[anti-EGFR]. Attributes of dexamethasone-(C21-phosphoramide)-[anti-EGFR] include a high dexamethasone molar incorporation-index, lack of extraneous chemical group introduction, retained EGFR-binding avidity (“targeted” delivery properties), and potential to enhance long-term pharmaceutical moiety effectiveness. Keywords: dexamethasone, anti-EGFR, organic chemistry reactions, synthesis, selective “targeted” delivery, covalent immunopharmaceuticals, EGFR